High-coercivity ThMn12-type monocrystalline Sm–Zr–Fe–Co–Ti particles by high-temperature reduction diffusion. (15th April 2021) - Gabay, A.M.; Hadjipanayis, G.C.
Abstract: The ThMn12 -type (Sm, Zr)1 (Fe, Co, Ti)12 compounds have the potential of powerful permanent magnets. Magnetically hard and anisotropic powders of such compound have been prepared by subjecting elemental oxides and Co mixed with Ca and CaO dispersant to a succession of high-energy ball-milling, reduction diffusion at 990–1220°C and repeated washing. The size of the resulting ThMn12 -type crystallites, their coercivity and fraction of monocrystalline particles were all found to increase with the reduction-diffusion temperature. Particles synthesized at 1220°C were highly monocrystalline with a mean size of 0.54 μm and, after a magnetic-field alignment, exhibited a coercivity of 1.26 T and a full-density-projected maximum energy product of at least 209 kJ/m 3 (26.3 MGOe). The strong positive effect of the reduction-diffusion temperature on the coercivity has been attributed to separation of the crystallites and to decrease in the incidence of structural defects. Graphical abstract: Image, graphical abstract